Harnessing public research for innovation in the 21st century : an international assessment of knowledge transfer policies - Arundel, Anthony; Athreye, Suma; Wunsch-Vincent, Sacha (Cambridge : Cambridge University Press, 2021)
Universities and public research institutes play a key role in enabling the application of scientific breakthroughs and innovations in the marketplace. Many countries - developed and developing alike - have implemented national strategies to support the application or commercialization of knowledge produced by public research organizations. Universities and public research institutes have introduced practices to support these activities, for instance by including knowledge transfer to promote innovation as a core part of their mission. As a result, a vital question for policymakers is how to improve the efficiency of these knowledge transfer practices to help maximize innovation-driven growth and/or to seek practical solutions to critical societal challenges. This book aims to develop a conceptual framework to evaluate knowledge transfer practices and outcomes; to improve knowledge transfer metrics, surveys and evaluation frameworks; and to generate findings on what works and what does not, and to propose related policy lessons. This book is also available as Open Access.
Title from publisher's bibliographic system (viewed on 19 Mar 2021).
Keywords: Academic spin-outs.; Technological innovations; Research institutes; Research, Industrial; Political planning